Ethnobotany of Medicinal Plants Used by Kathariya (Tharu) Community in Kailali District, Nepal - Khanal, Chetana; Neupane, Sudhir; Thapa Magar, Madhu Shudan (Journal of Plant Resources, 2022)
This study aims to document the traditional knowledge on medicinal use of plants by Kathariya (Tharu) community in Kailali district. Kathariya is one of the sub-group of the Tharu community whose culture and language is slightly different from other sub-groups. Traditional healers Guruwa of Kathariya community from five study sites viz. Sisaiya, Tappa, Udasipur, Pawera and Joshipur of Kailali were identified as key informants. Exploratory research design was adopted and interview method was used to collect the primary information through Semi-structured open-ended questionnaire. Altogether 70 species of plants used for medicinal purposes were documented. Sixteen species were found useful in cuts, wounds and swelling which is one of ten health issues categorized in the present study. Thirteen and Twelve species were recorded to be used in abdominal disorders and skin diseases respectively. The community usually mixes powder in measurement of two and half grains of each Barley and Black Pepper during preparations of medicine for oral route of consumption. Based on habit, highest number of plant species belongs to herbs (30 species). Among five study sites, highest number of species was recorded in Udasipur with 35 species. Regarding the parts of plant used, roots and leaves were found to be used often equally, which were represented by 24 species each. Achyranthes aspera, Euphorbia hirta, Azadirachta indica and Clerodendrom infortunatum were the most frequently used species. This study generated preliminary but crucial information which may open the avenue for utilization of biological resources. Further research leading to bio-prospecting is needed to utilize these resources.